Strengthening Infrastructure Governance for Investment and Service Delivery in Panama - World Bank (World Bank, Washington, DC, 2020)
Global evidence suggests better infrastructure governance results in more efficient spending and better growth outcomes at the national and subnational levels of government. Several studies (International Monetary Fund (IMF), 2015; OECD, 2015; World Bank 2014; OECD, 2013a) demonstrate that improvements in infrastructure governance can lead to substantial efficiency enhancements and enhanced infrastructure productivity over the life of the asset. Conversely, poor governance is a major reason why infrastructure projects fail to meet their timeframe, budget, and service delivery objectives. This report assesses the governance of the infrastructure sectors in Panama. Building on a dedicated infrastructure governance framework (see Section II), the report looks at the sector specific arrangements in electricity and water as well as the cross-cutting framework for infrastructure planning, procurement and delivery including for PPPs. The main recommendations of the report are presented in Section I below. Aimed at addressing Panama’s infrastructure governance bottlenecks, the recommendations specify the suggested timeline and priority.